Tema dan Nilai Moral dalam Karya Sastra Melayu Klasik “Hikayat Hang Tuah, Hikayat Raja Pasai, dan Hikayat Abdullah “ - Anisa Putri; Arvirelia Rahmatillah; Feby Oriza Sativa; Isfy Aprilian Nusen; Maya Aulia Sari; Vera Sardila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This discussion examines the themes and values ​​contained in classical Malay literary works focusing on several main works such as